(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The study aims to analyze the rehabilitation program for indexers in library department, the study will shed light on the role of the information and libraries in the indexing syllabi studied and his/her indexing skills and to what extent he/she keeps pace with modern developments, the study relied in achieving its goals on the descriptive analytical filed approach to analyze the indexing syllabi studied in the department, the study revolves around indexing department at the university Damascus, and monitoring those professional development programs for indexers, the study is based on the following tools: questionnaires and content analysis, the study has reached result, the most important recommendation were calling upon the libraries and information department at the universities of Damascus to quickly initiation to re-examine at their study programs, especially in courses that address issues of technical processing of information sources due to those frequent change taking place in this area, and initiation to development their websites of the internet, that provoked for school subjects to development their performance and help student to understand their subjects.